Masa depan perpustakaan seiring perkembangan revolusi industri 4.0 : mengevaluasi peranan pustakawan - Nora Junita Azmar (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
This article discusses the revolution of this 4.0 industry recently launched in Indonesia and it is impossible to do in the library for the near term, but it would be better if the Human Resources have been forged since now. As for librarians in the face of this 4.0 industrial revolution is to prepare knowledge, technology, information, communication and social skills, because again this revolution is successful if its human resources are also competent in their field. keywords: library, librarian, revolution, industry 4.0